The Eternal Return of Religion: jean-luc nancy on faith in the singular-plural. Issue 3 (4th July 2021) - Chabbert, Marie
Abstract: At the opening of the first volume of his Deconstruction of Christianity, Nancy argues that "The much discussed 'return of the religious, ' which denotes a real phenomenon, deserves no more attention than any other 'return'" (1). This statement may seem paradoxical in light of Nancy's extensive study of the logic of the return – including, of the divine – in texts such as "Of Divine Places, " Noli me tangere, Dis-Enclosure and Adoration . Nancy does pay considerable attention to something that, according to him, deserves none. In this paper, I examine Nancy's critique of the "return of religion" in detail and argue that it would be a mistake to assume that Nancy's understanding of the logic of the "return" is limited to the – largely uninteresting and even dangerous, indeed – return of the Same, just as it is a mistake to assume that the phenomenon known as the "return of religion" merely consists of the dialectical resurgence of a past religious fervour, a step backwards in history. According to Nancy, religion today returns in a way that radically breaks with the logic of the return of the Same and testifies to an eternal return of difference which, paraphrasing Nancy, opens religion to the limitlessness that constitutes its truth. It does, therefore, deserve our attention, yet only insofar as, paraphrasing Nancy, it opens religion to the limitlessness that constitutes its truth ( Dis-Enclosure 1), thereby providing us with new resources to think religion in the singular-plural today.